The positional parameter of EMG for transtibial prosthetic users / Khaled Nedal Mahmoud Sobh - Khaled Nedal, Mahmoud Sobh (2018)
Amputation is an operation that involves partial or total removal of a limb. Amputations are limited to the two main parts of the body (upper limb and lower limb) and each limb has its amputation levels. This study will focus on the lower limb amputation (transtibial amputee). Transtibial Amputations (TT Amp) is one of the most amputated types of the lower limb, also known as below-knee (BK) amputation. Prosthetic limbs are found and manufactured to serve those affected, by overcoming difficulties or challenges that may be encountered in their daily activities such as walking, jumping, squatting and other movements. One of the advance powered lower limb prostheses (transtibial) that improves the movement performance of the users of these limbs using electromyography (EMG) sensor known as C-LEG. The main challenge faced by the prosthetic limb is the position of the EMG sensor. EMG sensor within the socket in a fixed position sometimes leads to contact with inactive muscles, which causes reduction in efficiency of use. The aim of the study is to investigate the best positional parameter of EMG for transtibial prosthetic users (TTAmp) to be effective in multiple movement activities and compare with the normal human muscleï¿½s activities. DELSYS Trigno wireless EMG instrument was used in this study to achieve this aim. Ten non-amputee subjects and two transtibial amputee subjects were involved in this study. The surface EMG signals were recorded from two anterior and posterior below knee muscles; tibialis anterior (TA) and gastrocnemius lateral head (LG), and two anterior and posterior above knee muscles; rectus femoris (RF) and biceps femoris (BF) during five activities; muscles strengthening, flexion and extension, gait cycle (normal walking), descending the stairs and ascending the stairs. The result is that some muscles are active and useful in the performance of certain activities, but they are not effective in other activities, so it is difficult to rely entirely on the static positioning of the EMG sensor within socket due to the possibility of that sensor to be in contact with inactive muscle so there will be a gap in the control leads to decrease the functional efficiency of the powered prostheses. There is, therefore, a need to put the EMG sensor out of the socket to reduce this gap in prosthetic limbs control by amputees and to ensure that each sensor is connected to an active muscle of which through the EMG signal from that active muscles can increase the control efficiency.